Development of an Application for Screening Diabetes and Hypertension Risk Groups - Maneelert, Chulawalee (Community and Social Development Journal, 2021)
The purpose of this research was to develop an application for screening diabetes and hypertension risk groups and to study sample satisfaction with the application for screening diabetes and hypertension risk groups. The sample group consisted of a sample group evaluating the effectiveness of the application for screening diabetes and hypertension risk groups, including 5 community representatives and academics from higher education institutions, obtained through a specific method. 30 samples who evaluated the application for screening diabetes and hypertension risk groups were obtained by simple random sampling. The research instruments consisted of interview form, the application for screening diabetes and hypertension risk groups, application performance evaluation form, and a satisfaction questionnaire from a sample group on the application. The statistics used were mean and standard deviation. The results of this research showed that the overall efficacy values of the experts with mean of 4.26, the standard deviation of 0.61, which was very appropriate. The application for screening diabetes and hypertension risk groups can classify users into 7 groups and make recommendations for health behavior modification. When the application was tested by the sample group, overall satisfaction with mean of 4.47, the standard deviation of 0.66, which was at a high level. Competence of the community has the ability to take care of their own health, monitoring and controlling the factors of impact on health in a timely manner.